Hamiltonian approach to the charge transfer statistics of Kondo quantum dots contacted by a normal metal and a superconductor - Soller, Henning; Komnik, Andreas (Physica. E, Low-dimensional systems & nanostructures, 2011)
We analyze the full counting statistics (FCS) of quantum dots in the Kondo regime contacted by normal and superconducting leads or an STM tip. To describe the Kondo resonance we use an effective model for the quantum dot in the Kondo regime in combination with the FCS for tunneling contacts calculated using the Hamiltonian approach. We show that the situation of weak coupling to the superconducting electrode in the case of superconductor gap being larger than the Kondo resonance width can be easily handled and verify the method by comparing our theoretical predictions to experimental data. This allows us to make predictions for the noise and cross-correlation in setups involving a superconductor. We find that a positive cross-correlation is possible in the case of a superconductor and two normal leads contacted via two quantum dots in the Kondo regime.
Gesehen am 18.10.2022